Pengaruh Persepsi Nilai, Kualitas Produk, dan Inovasi Layanan terhadap Pengguna Selfphoto Studio – Potokita Prapen di Surabaya - Shaluna Mei Ardhana; Awin Mulyati; Diana Juni Mulyati (Lembaga Pengembangan Kinerja Dosen, 2025)
Self-photo studio is a modern photography trend that is growing rapidly among the younger generation, because it offers a private, flexible, and aesthetic photo experience without the help of a photographer. One of the business actors in this field is Selfphoto Studio - Potokita Prapen Surabaya, which has attracted the attention of many users. However, customer satisfaction is not always met because of the gap between expectations and the reality of the services provided. This study aims to determine the effect of Perceived Value, Product Quality, and Service Innovation on user satisfaction at Selfphoto Studio - Potokita Prapen branch in Surabaya. This study uses a quantitative approach with data collection techniques through the distribution of E-questionnaires. The number of respondents in this study was 100 Potokita Prapen users who were selected using a purposive sampling technique. The results of the study showed that perceived value, product quality, and service innovation had a positive and significant effect on user satisfaction, both partially and simultaneously. The results of the study showed that perceived value, product quality, and service innovation had a positive and significant effect on user satisfaction, both partially and simultaneously. These findings provide implications for the management of Selfphoto Studio - Potokita to pay more attention to these factors in order to increase customer satisfaction and loyalty..